Kokilaben Dhirubhai Ambani Vidyamandir, Jamnagar - Sharma, Rajeev (London : SAGE Publications Ltd, 2017)
In the afternoon of October 19th 2013, Mr. Sundaram was in a pensive mood after being accorded a very warm and affectionate farewell by all the teachers and staff of Kokilaben Dhirubhai Ambani Vidyamandir (KDAV). After a period of five years as principal of the school, Sundaram was scheduled to retire on October 31st, 2013. While accolades were overwhelming, he also had a sense of satisfaction about being able to bring about a change in the teaching and learning process in grades I to V. The change involved switching from four-times-a-year examination system to continuous assessment and feedback round the year, replacing marks with grades, introducing worksheets generated by teachers in place of text books and integrating activity-based learning in the teaching-learning process.
Originally published: Sharma, R. (2014). Kokilaben Dhirubhai Ambani Vidyamandir, Jamnagar. RJMC0030. Ahmedabad: Indian Institute of Management, Ahmedabad.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Kokilaben Dhirubhai Ambani Vidyamandir; Educational change -- India -- Case studies; Educational innovations -- India -- Case studies; Education, Elementary -- India -- Case studies; Educational tests and measurements -- India -- Case studies